Avaliação do potencial de produção de metano a partir da codigestão anaeróbia de resíduos de alimentos e aguapé: escala piloto - Machado, Francisca Lívia de Oliveira (2024)
Sustainable solutions for the management of organic waste and the reduction of greenhouse gas (GHG) emissions have motivated research to optimize the application of anaerobic digestion and biogas production as a strategic alternative for decarbonizing the energy matrix. In this context, the present study evaluated the methane production potential from the anaerobic digestion of food waste and water hyacinth on a pilot scale. A 1300L biodigester with a 1000L was used, operating in a semi-continuous mode, with an organic loading rate (OLR) ranging from 0.29 to 0.35 kg VS.m-3d-1. The process started with the mono-digestion of food waste (Phase 1) and subsequently progressed to co-digestion with untreated water hyacinth (Phase 2), dried water hyacinth (Phase 3), and a mixture of untreated and treated water hyacinth at a 50% ratio between the fractions (Phase 4). The experiment lasted 399 days. Throughout the experiment, the following control and efficiency parameters were monitored: pH, temperature, alkalinity, volatile fatty acids (VFA), chemical oxygen demand (COD), total organic carbon (TOC), total solids (TS), volatile solids (VS), ammonia (NH4), total Kjeldahl nitrogen (TKN), biogas volume, and methane percentage in the biogas. Bottom sludge samples were characterized in terms of metals, pH, TS, VS, fixed solids (FS), alkalinity, VFA, NH4, organic nitrogen, TKN, inorganic carbon, and organic carbon. The initial and final digestate from each stage, along with one of the six bottom sludge samples, were characterized using Nuclear Magnetic Resonance (NMR) spectroscopy for the detection of organic compounds. Given the extensive number of variables obtained in the four stages of the study, unsupervised multivariate statistical analysis using Principal Component Analysis (PCA) and supervised analysis using Partial Least Squares Discriminant Analysis (PLS-DA) were performed to reduce data dimensionality and explain the majority of the data variability, thereby facilitating the interpretation of the results. The average biogas yields for each stage were 0.16789 Nm3/kg VS, 0.09506 Nm3/kg VS, 0.22987 Nm3/kg VS, and 0.18772 Nm3/kg VS for stages 1, 2, 3, and 4, while the average methane percentages were 57.85%, 56.58%, 56.84%, and 57.52%, respectively. Stage 4 showed higher COD and SV removal, with no statistically significant difference compared to Stage 3, which achieved higher accumulated biogas volume and methane yield, in addition to eliminating the need for treating the entire water hyacinth biomass.